Clinical and Laboratory Parameters of GonadotropinReleasing Hormone Analog Treatment Effectiveness in Children with Precocious Puberty (Clinics, 2019)
OBJECTIVE: There are no doubts about the clinical benefits of treatment with GnRH analogs for patients diagnosed with central precocious puberty (CPP). However, laboratory monitoring of CPP is still a matter of considerable controversy in the literature. Therefore, the main objective of this study was to evaluate the cut-off values of stimulated LH that determine gonadotrophic suppression. METHODS: Twenty-four girls, on treatment with leuprorelin acetate (LA) at 3.75 mg IM every 28 days, were studied. The clinical parameters used to indicate clinical effectiveness were regression or maintenance of sexual characteristics according to the Tanner stage, growth velocity reduction, reduction or maintenance of the difference between bone age and chronological age and maintenance or improvement of the final height prediction. For the laboratory effectiveness test, basal estradiol, LH, and FSH levels were collected before and 1 and 2 h after the administration of 3.75 mg LA. RESULTS: Eleven girls showed improvement in all clinical parameters, and their effectiveness tests were compared to those of the other patients to calculate the cut-off values, which were p3.64 IU/L (p=0.004*) for LH after 1 h and p6.10 IU/L (po0.001*) for LH after 2 h. CONCLUSION: The LH response after the LA stimulation test, associated with clinical data and within a context of CPP, constitutes a reliable and feasible resource and can assist in monitoring the effectiveness of treatment.